Graduating With Honors in Resilience: Creating a Whole New Doctor - John Paul Mikhaiel MD; Jack Pollack MD; Emory Buck MD; Matt Williams MD; Aisha Lott MD, MA; John C Penner MD; Margaret Ann Cary MD, MBA, MPH, PCC (SAGE Publishing, 2020)
Background Although coaching programs have become a prominent piece of graduate medical education, they have yet to become an integral part of undergraduate medical education. A handful of medical schools have utilized longitudinal coaching experiences as a method for professional identity formation, developing emotional intelligence and leadership. Objective We developed A Whole New Doctor (AWND), a medical student leadership development and coaching program at Georgetown University, with the aim of fostering resilience, leadership, and emotional intelligence at the nascent stage of physician training. To our knowledge, ours is the only program that is largely student-managed and uses certified executive coaches in the medical student population. Methods Cohort 1 of AWND started in October 2016. For each cohort, we hold a kickoff workshop that is highly interactive, fast-paced and covers coaching, complex thinking, reflective writing, and a coaching panel for Q&A. Following the workshop, students work with coaches individually to address self-identified weaknesses, tensions, and areas of conflict. We believe the program's student-driven nature provides a new structural approach to professional development and leadership programs, offering students a simultaneously reflective and growth-oriented opportunity to develop essential non-technical skills for physician leaders. Results Of the 132 students in the program, 107 have worked with one of our coaches (81%). Student testimonials have been uniformly positive with students remarking on an increased sense of presence, improvements in communication, and more specific direction in their careers. Conclusion Our pilot coaching program has received positive feedback from students early in their medical training. It will be important to further scale the program to reach an increasing number of students and quantitatively evaluate participants for the long-term effects of our interventions.